Machinery of dissent: Exploring the techno-social practices of modern protests - Alesia Rudnik (Internet Policy Review, 2024)
Protest mobilisation and coordination require competences that extend beyond political leadership and communication. Technology, which has become a daily part of humanity, pushes protest leaders to obtain skills in navigating social media to achieve effective communication and leadership. Labour practices behind protest mobilisation are gradually complexifying and require a broadening of our understanding of human actions behind the implementation of technological solutions in the context of political protests. Focusing on the example of the Belarusian protests of 2020, this article examines the human and non-human labour behind the production of protest mobilisation content, protest coordination, and protest reporting. Based on semi-structured interviews with 18 respondents, the paper is the first to examine the practices and routines of Telegram channel editors and moderators, activists, politicians, and marketing specialists. The analysis contributes to our understanding of protest-related labour, which is often unseen and divided between humans and technology, and its consequences for the protest movement.
Keywords: 300; Science and technology studies (STS); Labour; Protest; Belarus